(untitled) (Research, Society and Development, 2022)
The present article aims to evaluate which are the factors from biopsychosocial basis and obstetrician aspects and assistance in health are associated with the practice of early weaning therefore being able to assist the behaviors on the subject and increase the breastfeeding index. It is a literature integrative review, descriptive research, qualitative approach and deductive method performed by the electronic data base PubMed, MEDLINE, LILACS, VHL, BDENF e SciELO, using the index terms “aleitamento materno/breatsfeeding” and “desmame/weaning” with the boolean operators “e/AND”. In the initial search there were found 4407 articles. After applying the criteria of eligibility and reading, 22 articles were analyzed. The exclusive breastfeeding rates fluctuate between 14,8% and 98,1%. The main factors that had association with early weaning were: older age of the child, maternal work, use of dairy compound in the hospital, use of pacifier, mom with depressive symptoms. In contrast, mothers with past experience, paternal support, medium and high levels of self-efficacy, being in EBF in the hospital discharge and receive professional support and incentive in prenatal, immediate postpartum and late puerperium were protection factors to breastfeeding. Breastfeeding is determinate by multiple factors. The variables of assistance basis are a central aspect when breastfeeding is analyzed and the focus on maternal perception is necessary for the establishment and success of breastfeeding through understanding of obstacles, uncertainly and dissatisfaction with the process.